Frame rate free image velocimetry for microfluidic devices - Keinan, Eliezer (AIP Publishing LLC, 2013)
Here, we introduce Streamline Image Velocimetry, a method to derive fluid velocity fields in fully developed laminar flow from long-exposure images of streamlines. Streamlines confine streamtubes, in which the volumetric flow is constant for incompressible fluid. Using an explicit analytical solution as a boundary condition, velocity fields and emerging properties such as shear force and pressure can be quantified throughout. Numerical and experimental validations show a high correlation between anticipated and measured results, with R(2) > 0.91. We report spatial resolution of 2 μm in a flow rate of 0.15 m/s, resolution that can only be achieved with 75 kHz frame rate in traditional particle tracking velocimetry.